1998
DOI: 10.1016/s0030-4018(98)00051-0
|View full text |Cite
|
Sign up to set email alerts
|

Coherent light transmission by a dew pattern

Abstract: We study both theoretically and experimentally the transmission of coherent light by a drop pattern (dew). The theory is based on the Kirchhoff scalar approach to diffraction. The polarization of the diffracted wave in the zero diffraction order is analyzed separately. The intensity in the zero diffraction order in the far zone is an oscillatory function of the drop size. These oscillations are observed with a pattern of water drops growing on glass. The model allows the evolution of the important parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 12 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Among these devices, some are used for ecological purposes. Thus for instance, sensors that measure the amount of dew by electrical means, such as the leaf wetness sensors (Gillepsie & Duan, 1987) or those that measure the dew by optical means, such as by light transmission (Nikolayev, Sibille, & Beysens, 1998) or by the change in the spectral reflectance . Additionally, there are many condensers aiming to measure dew and fog, mainly exploring their use for harvesting atmospheric water for human use.…”
Section: Non-rainfall Water: Definition and Measurement Techniquesmentioning
confidence: 99%
“…Among these devices, some are used for ecological purposes. Thus for instance, sensors that measure the amount of dew by electrical means, such as the leaf wetness sensors (Gillepsie & Duan, 1987) or those that measure the dew by optical means, such as by light transmission (Nikolayev, Sibille, & Beysens, 1998) or by the change in the spectral reflectance . Additionally, there are many condensers aiming to measure dew and fog, mainly exploring their use for harvesting atmospheric water for human use.…”
Section: Non-rainfall Water: Definition and Measurement Techniquesmentioning
confidence: 99%
“…Spectral measurements in the atmospheric window have already shown that the average emissivity of a plastic substrate increases when wet. [20] In the visible spectrum, the impact of dropwise condensation on the trajectory and polarization of light modified by an assembly of droplets, covering windows, [22,23] solar panels, or greenhouses [24] have been previously studied. A lack of knowledge remains regarding the spectrally-resolved effective emissivity of a wet surface in the MWIR spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…Breath figures and droplet growth rates during the condensation process are relevant in the context of a number of applications, notably for water harvesting in desert areas, for heat transfer processes and for the formation of dew on transparent surfaces [21,22,23,24]. The impact of dew on transparency can be problematic when it impacts the efficacy of helmet visors, diving masks or car headlights where the light emission is affected by the presence of dew.…”
Section: Introductionmentioning
confidence: 99%